DRINKS OF THE PEOPLES OF DAGESTAN IN THE 19TH – EARLY 20TH CENTURIES - Ramazanova, Zoa Buttaevna; Sulejmanova, Sevda Alievna (History, Archeology and Ethnography of the Caucasus, 2021)
The purpose of the article is to analyze the drinks of the peoples of Dagestan in the period under study, which represent a certain independent subsystem within the general food system. The article was written based on the material of the ethnographic expeditions of 1985-2005. in the districts of Dagestan.The relevance of the research topic is due to the environmental crisis, initiated by the growth of industrialization, increased antagonism. an appeal to the historical experience of the peoples of Dagestan makes it possible to identify positive examples of an eco-oriented attitude towards the natural environment of the Dagestanis in the period under study. The heightened interest in the national origins of modern culture, in particular, in everyday culture, which has emerged recently; the location of Dagestan in the contact zone, in which local traditional forms and phenomena are intertwined with European and Near Eastern ones, also actualize the topic raised in the article.The ethnographic materials of the author became the sources for the study. Field ethnographic materials on the peoples of Dagestan are considered from the point of view of a special and comprehensive study of drinks as a specific subsystem within the general nutrition system. The generalization of information from sources on ethnography made it possible to get an idea of ​​the place and composition of the drinks of the peoples of Dagestan, about the stability of traditions, about the dependence on natural and geographical conditions and economy.Methodology of the work. The research is based on the principle of historicism, which makes it possible to analyze the traditional drinks of the peoples of Dagestan in the context of socio-cultural changes. Also, the method of logical research has become important in the article, the task of which is to reveal the role that the individual elements of the system play in the whole. Along with general scientific methods, private research methods were used in the work: identifying a specific, descriptive method, a method of generalization. The field of application of the research results is in educational and research activities.
Keywords: The peoples of Dagestan; beverages; intoxicating drinks; bread drinks; milk drinks; water.